2015
DOI: 10.12816/0024679
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative / Nitrosative Stress in Rats Subjected to Focal Cerebral Ischemia / Reperfusion

Abstract: Background: Ischemic stroke usually initiates inflammation and oxidative/nitrosative stress leading to neuronal death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
(31 reference statements)
1
21
0
Order By: Relevance
“…The local accumulation of NO is also involved in the inflammatory cascade after cerebral ischemia [ 48 , 49 ]. This mediator enhances cell adhesion molecules expression on endothelial cells and promotes adhesion and transendothelial migration of immune cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The local accumulation of NO is also involved in the inflammatory cascade after cerebral ischemia [ 48 , 49 ]. This mediator enhances cell adhesion molecules expression on endothelial cells and promotes adhesion and transendothelial migration of immune cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the brain is highly susceptible to free radical mediated insult owing to its high lipid content [21]. ROS levels are elevated in the cerebral vasculature during reperfusion period [22], and suspected to be an underlying cause of post-ischemic endothelial dysfunction, however, their enzymatic source(s) is yet to be defined [11]. The (nicotinamide adenine dinucleotide phosphate) NADPH oxidases are the only enzymes yet discovered with the primary function of generating superoxide and ROS in the cerebral vasculature under physiological conditions [23].…”
Section: Oxidative/nitrosative Stress In Cerebral Ischemiamentioning
confidence: 99%
“…Oxidative/nitrosative stresses are modulated by enzyme systems such as SOD and the nitric oxide synthase (NOS) family [25]. Mice with enhanced expression of SOD show reduced injury after cerebral ischemia, whereas those with a deficiency show increased injury, proving that excessive oxygen radical production is fundamental to ischemic brain injury, while in case of NOS activation during ischemia, superoxide reacts avidly with NO leading to decrease NO bioavailability and the formation of peroxynitrite a highly reactive and damaging species that causes nitration of tyrosine residues on proteins [11]…”
Section: Oxidative/nitrosative Stress In Cerebral Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by an imbalance between the generation of reactive oxygen species (ROS) and the capacity of the intrinsic antioxidant defence system of the cerebral system [5]. In both experimental and clinical studies, this balance has shown increase in favour of oxidants in cases of transient ischaemia [6,7]. Several endogenous and exogenous antioxidants are used to neutralize and protect the brain from free radicals by maintaining the redox balance [8].…”
Section: Introductionmentioning
confidence: 99%